Cooperation & Security Dilemma In The South China Sea - Widian, Rizky; Arimadona, Arimadona (Global Strategis, 2018)
This article will talk about security dilemma and offense-defense balance in the South China Sea. The rising of China's power in the South China Sea that facilitate the process security dilemma makes cooperation between claimant countries become more difficult. Regarding this matter, it's important to explain why cooperation in the area is difficult in the midst of many literatures that advocated cooperation as the tools for conflict management in the South China Sea. In order to form an ideal explanation, this article will refer to the concepts of security dilemma and offense-defense balance by Robert Jervis. The data in this article will be explored using qualitative research method of literature review to illustrate the distribution of power in the region. Through the data exploration, this article found that China's offensive power in the South China Sea is large enough to cause the sense insecurity and security dilemma. Thus, this article argue that the security dilemma caused by China's offensive power capability in the South China Sea is the main the reason that inhibiting cooperation between claimant states.